2022
DOI: 10.3390/ijms232214268
|View full text |Cite
|
Sign up to set email alerts
|

Immobilization of Lipase B from Candida antarctica in Octyl-Vinyl Sulfone Agarose: Effect of the Enzyme-Support Interactions on Enzyme Activity, Specificity, Structure and Inactivation Pathway

Abstract: Lipase B from Candida antarctica was immobilized on heterofunctional support octyl agarose activated with vinyl sulfone to prevent enzyme release under drastic conditions. Covalent attachment was established, but the blocking step using hexylamine, ethylenediamine or the amino acids glycine (Gly) and aspartic acid (Asp) altered the results. The activities were lower than those observed using the octyl biocatalyst, except when using ethylenediamine as blocking reagent and p-nitrophenol butyrate (pNPB) as substr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 94 publications
0
11
0
Order By: Relevance
“…Physical and covalent bonds are among the support binding methods [ 23 , 24 ]. The physical unions are carried out on hydrophobic materials, weak Van der Wals unions, or by encapsulation using polymers, biopolymers, or a combination of both [ 25 ].…”
Section: Upstream Bioprocessingmentioning
confidence: 99%
See 1 more Smart Citation
“…Physical and covalent bonds are among the support binding methods [ 23 , 24 ]. The physical unions are carried out on hydrophobic materials, weak Van der Wals unions, or by encapsulation using polymers, biopolymers, or a combination of both [ 25 ].…”
Section: Upstream Bioprocessingmentioning
confidence: 99%
“…Another strategy to stabilize and reuse the enzyme is immobilization, which consists of fixing the enzyme on a material (binding to support) or forming cross-linked enzyme aggregates (CLEAs) between the same molecules [ 21 , 22 ]. Physical and covalent bonds are among the support binding methods [ 23 , 24 ]. The physical unions are carried out on hydrophobic materials, weak Van der Wals unions, or by encapsulation using polymers, biopolymers, or a combination of both [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Conceptually, an immobilized enzyme can be defined as an enzyme that is physically confined or localized to a particular solid support, whose catalytic activities are maintained, and can be used repeatedly and continuously. , In scientific research, many methods of enzyme immobilization have been reported, including adsorption, covalent bonding, cross-linking, and entrapment; each has advantages and disadvantages. ,, Owing to the improved stability, reusability, and high enzyme retention of the proposed supports, more and more types of materials have been used as supports to immobilize various enzymes . To date, many carriers have been used for immobilization including natural or synthetic polymers, copolymers, hydrogels, beads, blends, nanofibers, nanoparticles, composites, metal–organic frameworks, , etc. We refer readers to several recent review articles that comprehensively review these areas (method and support). , Although the scientific literature is full of reports on new carrier supports and new approaches to immobilize enzymes, most of them are not even suitable for enzyme immobilization as the immobilization method and carrier used are insufficient to improve the enzyme properties of the matrix.…”
Section: Introductionmentioning
confidence: 99%
“…, zeolites, mesoporous silica, polymers) have been used as host materials for enzyme immobilization. 17–20 Their large specific surface area is beneficial for enzyme capacity, and their porosity may improve the diffusion of the substrate.…”
Section: Introductionmentioning
confidence: 99%
“…15,16 Additionally, because of their large specific surface area and porosity, many porous materials (e.g., zeolites, mesoporous silica, polymers) have been used as host materials for enzyme immobilization. [17][18][19][20] Their large specific surface area is beneficial for enzyme capacity, and their porosity may improve the diffusion of the substrate.…”
Section: Introductionmentioning
confidence: 99%